Metode Pembelajaran Studi Islam di Sekolah Tinggi Agama Islam (STAI) Madrasah Arabiyah (MA) Bayang Kabupaten Pesisir Selatan - Syafrijal, Syafrijal; Yunus, Muhammad (Universitas Lampung, 2024)
This research aims to analyze and describe the implementation of Islamic studies learning methods at the Islamic High School (STAI) Madrasah Arabiyah (MA) Bayang, Pesisir Selatan Regency. The research focus includes three main learning methods applied, namely textual-contextual methods, problem-based learning, and collaborative learning. The research uses a qualitative approach with analytical descriptive methods, with data collection techniques through participant observation, in-depth interviews with 5 lecturers and 15 students, as well as documentation studies. Data analysis uses the Miles and Huberman interactive model. The research results show that the implementation of learning methods at STAI MA Bayang is integrative and adaptive, by combining the three methods according to the characteristics of the course. The textual-contextual method is effective in developing a comprehensive understanding of religious texts, problem-based learning is successful in improving analytical skills in dealing with contemporary issues, and collaborative learning encourages active learning through interaction between students. Despite facing challenges such as limited resources and diversity of student backgrounds, institutions have succeeded in overcoming them through various development programs and utilization of learning technology.Penelitian ini bertujuan untuk menganalisis dan mendeskripsikan implementasi metode pembelajaran studi Islam di Sekolah Tinggi Agama Islam (STAI) Madrasah Arabiyah (MA) Bayang, Kabupaten Pesisir Selatan. Fokus penelitian meliputi tiga metode pembelajaran utama yang diterapkan yaitu metode tekstual-kontekstual, problem-based learning, dan collaborative learning. Penelitian menggunakan pendekatan kualitatif dengan metode deskriptif analitis, dengan teknik pengumpulan data melalui observasi partisipatif, wawancara mendalam dengan 5 dosen dan 15 mahasiswa, serta studi dokumentasi. Analisis data menggunakan model interaktif Miles dan Huberman. Hasil penelitian menunjukkan bahwa implementasi metode pembelajaran di STAI MA Bayang bersifat integratif dan adaptif, dengan memadukan ketiga metode sesuai karakteristik mata kuliah. Metode tekstual-kontekstual efektif dalam mengembangkan pemahaman komprehensif terhadap teks keagamaan, problem-based learning berhasil meningkatkan kemampuan analitis dalam menghadapi isu kontemporer, dan collaborative learning mendorong pembelajaran aktif melalui interaksi antar mahasiswa. Meskipun menghadapi tantangan seperti keterbatasan sumber daya dan keragaman latar belakang mahasiswa, institusi berhasil mengatasinya melalui berbagai program pengembangan dan pemanfaatan teknologi pembelajaran.